2020
DOI: 10.1037/rev0000190
|View full text |Cite
|
Sign up to set email alerts
|

The Bayesian sampler: Generic Bayesian inference causes incoherence in human probability judgments.

Abstract: Human probability judgments are systematically biased, in apparent tension with Bayesian models of cognition. But perhaps the brain does not represent probabilities explicitly, but approximates probabilistic calculations through a process of sampling, as used in computational probabilistic models in statistics. Naïve probability estimates can be obtained by calculating the relative frequency of an event within a sample, but these estimates tend to be extreme when the sample size is small. We propose instead th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
190
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(202 citation statements)
references
References 119 publications
(249 reference statements)
7
190
5
Order By: Relevance
“…However, such theories might be modified in light of these results. For example, rather than aggregating across multiple simulation runs to make a probabilistic inference, people might use some type of biased aggregation scheme that results in judgment errors (Zhu, Sanborn, & Chater, 2020). It remains to be seen whether this biased aggregation approach can provide a simultaneous account of all the other documented phenomena in intuitive physical reasoning.…”
Section: Discussionmentioning
confidence: 99%
“…However, such theories might be modified in light of these results. For example, rather than aggregating across multiple simulation runs to make a probabilistic inference, people might use some type of biased aggregation scheme that results in judgment errors (Zhu, Sanborn, & Chater, 2020). It remains to be seen whether this biased aggregation approach can provide a simultaneous account of all the other documented phenomena in intuitive physical reasoning.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al (2020) showed that a number of identical mean predictions can be derived from an even more “rational” model, the Bayesian sampler . Zhu et al’s starting point is that with small samples, reading off relative frequencies cannot be quite right.…”
Section: Probability Judgment By Samplingmentioning
confidence: 99%
“…These reliable matches and mismatches between human judgment and probability theory form a challenge to nonsampling models of probability distortion; Costello and Watts (2014 have shown how a sampling model captures both the distortions and the patterns in human probability judgments-demonstrating that these judgments are, as they put it, "surprisingly rational" after all and that irrational judgments are the result of noise. Zhu et al (2020) showed that a number of identical mean predictions can be derived from an even more "rational" model, the Bayesian sampler. Zhu et al's starting point is that with small samples, reading off relative frequencies cannot be quite right.…”
Section: Probability Judgment By Samplingmentioning
confidence: 99%
See 2 more Smart Citations